An anesthesia protocol for robust and repeatable measurement of behavioral visceromotor responses to colorectal distension in mice - Zhang, Shaopeng; Chen, Longtu; Feng, Bin (Frontiers in Pain Research, 2023)
Introduction Visceral motor responses (VMR) to graded colorectal distension (CRD) have been extensively implemented to assess the level of visceral pain in awake rodents, which are inevitably confounded by movement artifacts and cannot be conveniently implemented to assess invasive neuromodulation protocols for treating visceral pain. In this report, we present an optimized protocol with prolonged urethane infusion that enables robust and repeatable recordings of VMR to CRD in mice under deep anesthesia, providing a two-hour window to objectively assess the efficacy of visceral pain management strategies. Methods During all surgical procedures, C57BL/6 mice of both sexes (8–12 weeks, 25–35 g) were anesthetized with 2% isoflurane inhalation. An abdominal incision was made to allow Teflon-coated stainless steel wire electrodes to be sutured to the oblique abdominal musculature. A thin polyethylene catheter (Φ 0.2 mm) was placed intraperitoneally and externalized from the abdominal incision for delivering the prolonged urethane infusion. A cylindric plastic-film balloon (Φ 8 mm x 15 mm when distended) was inserted intra-anally, and its depth into the colorectum was precisely controlled by measuring the distance between the end of the balloon and the anus. Subsequently, the mouse was switched from isoflurane anesthesia to the new urethane anesthesia protocol, which consisted of a bout of infusion (0.6 g urethane per kg weight, g/kg) administered intraperitoneally via the catheter and continuous low-dose infusion throughout the experiment at 0.15–0.23 g per kg weight per hour (g/kg/h). Results Using this new anesthesia protocol, we systematically investigated the significant impact of balloon depth into the colorectum on evoked VMR, which showed a progressive reduction with increased balloon insertion depth from the rectal region into the distal colonic region. Intracolonic TNBS treatment induced enhanced VMR to CRD of the colonic region (>10 mm from the anus) only in male mice, whereas colonic VMR was not significantly altered by TNBS in female mice. Discussion Conducting VMR to CRD in anesthetized mice using the current protocol will enable future objective assessments of various invasive neuromodulatory strategies for alleviating visceral pain.